A Study On AI-Driven Solutions for Cloud Security Platform - Menaga, Segar; Mohamad Fadli, Zolkipli (INTI International University, 2024)
Cloud computing has developed as a reliable approach to adopting various services inherent in data management but has its weaknesses in terms of security risks such as unauthorized access, data leakage or any other threats from insiders. This paper examines the role of AI in the improvement of cloud security with specific emphasis on deep learning, ensemble learning and lightweight AI approaches. Cognitive tasks comprise integration, computational cost, and the ethical effect of the algorithm are identified and discussed. Real-world applications and possibilities for further development, such as federated learning and XAI, are also described in order to give recommendations for the effective application of AI-based cloud security. Finally, this research seeks to help organizations protect cloud structures and resources using intentioned AI solutions.